Enhanced Temporal Convolutional Networks for Robust, Efficient Time Series Classification - Alekhya, Dasari; Haritha, Donavalli (Journal of Neonatal Surgery, 2025)
Time interdependence and different sequence lengths make time series data categorization still a difficult problem in machine learning. This article offers a better Temporal Convolutional Network (TCN) design that uses dilated causal convolutions and residual connections to solve these issues. Across many benchmark datasets, we methodically contrast our approach with conventional techniques like Long Short-Term Memory (LSTM) networks, Gated Recurrent Units (GRUs), and 1D Convolutional Neural Networks (CNNs). Experimental findings show that our TCN implementation outperforms traditional methods in terms of classification accuracy, computational efficiency, and resilience to varied sequence lengths. Along with ablation experiments confirming our design choices, we offer thorough examination of architectural options like kernel size, dilation factors, and residual block design. Aiming for uses from healthcare monitoring to industrial sensor data analysis, the suggested architecture has specific strength in encapsulating multivariate time series data's short- and long-term dependency.